Free versus subsidised healthcare: options for fee exemptions, access to care for vulnerable groups and effects on the health system in Burkina Faso - Maurice Yaogo (BMC, 2017)
Abstract Background The many forms of healthcare fee exemptions implemented in Burkina Faso since the 2000s have varied between total exemption (free) and cost subsidisation. This article examines both options, their contextual variations and the ways in which they affect access to healthcare for vulnerable people as well as the operation of the health system. This research is part of an interdisciplinary regional program on the elimination of user fees for health services in West Africa (Burkina Faso, Mali and Niger). Method A conceptual framework and a chronological review of policy interventions are used as references to summarise the results of the three qualitative studies presented. Historical reference points are used to describe the emergence of healthcare fee exemption policies in Burkina Faso and the events that influenced their adoption. The joint analysis of opinions on options for fee exemption focuses on the different types of repercussions on access to healthcare and the operation of the health system. Results In conjunction with the twists and turns of the gradual development of a national health policy and in response to international recommendations, healthcare fee exemptions have evolved since colonisation. The limitations of the changes introduced with cost recovery and the barriers to healthcare access for the poorest people led to the adoption of the current sectorial fee exemptions. The results provide information on the reasons for the changes that have occurred over time. The nuanced perspectives of different categories of people surveyed about fee exemption options show that, beyond the perceived effects on healthcare access and the health system, the issue is one of more equitable governance. Conclusions In principle, the fee exemption measures are intended to provide improved healthcare access for vulnerable groups. In practice, the negative effects on the operation of the health system advocate for reforms to harmonise the changes to multifaceted fee exemptions and the actual needs to promote effectiveness and sustainability.